Pengembangan Plugin Penjadwalan Seminar Pada Web Jurusan Ilmu Komputer Berbasis Wordpress - Amin Nurul Fatah; Didik Kurniawan; Anie Rose Irawati (Jurnal Komputasi, 2016)
The excess of plugin is more practical because it does not need to create a web from the base, and web with attached plugin becomes better. Furthermore small in storage capacity. Plugin of seminar which has built has advantages from the system that already exist, conventional system is still using whiteboards and paper, plugin is successfully implemented into the web of Computer Science Department and dissemination of information about seminar schedule become more optimal, as well this plugin has facility of reminder for lectures and college student that related to the seminar.